RANCANG BANGUN APLIKASI PENDAFTARAN KEGIATAN PROGRAM MBKM MENGGUNAKAN FRAMEWORK LARAVEL - Qinthara Sephira (2021)
The registration process for the MBKM program at the Faculty of Computer Science still uses google forms as a medium for filling out forms. Information technology is needed to create a system in the form of an application for registration of MBKM program activities. The application for registration of MBKM program activities carried out in this research uses the Laravel framework, which aims to build a website for students registering for the MBKM program, selecting supervisors, obtaining selection information, and making it easier to manage registrant data. The research methodology used in this research is the prototyping methodology which serves as a description of the application created, then it is designed using UML (Unified Modeling Language) and it is built using the Laravel framework with MySQL as the database server. The result obtained from this study is a finished application which is a registration application for MBKM program activities that can be used by students, admins, supervisors, vice deans of field 3, and heads of study programs. With this application, it can minimize existing problems such as duplication of data and human error.